Синтез и исследование люминесцентных свойств медьсодержащего соединения на основе 3-метилбензотиазол-2-тиона - Бирюков, Данил Александрович (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
The synthesis of a coordination compound of copper (II) with 3-methylbenzothiazole-2-thion is considered, the structure of the compound is investigated by spectral analysis methods. During the analysis, the peculiarity of the formation of this compound was established. It was found that the organic ligand is coordinated to the copper ion (Cu2+) by nitrogen and sulfur atoms to form N-Cu-S bonds. The luminescence of the synthesized compound (Xmax = 518 nm) was studied, the intensity of which exceeds the intensity of the initial organic compound (ligand).